Universal credit in Northern Ireland: What will its impact be, and what are the challenges? - James Browne; Barra Roantree (Institute for Fiscal Studies (IFS), 2013)
This is the first of two reports examining welfare reform and poverty in Northern Ireland. The research was funded by the Office of the First Minister and Deputy First Minister, Northern Ireland and the ESRC Centre for the Microeconomic Analysis of Public Policy.
Keywords: 330